2002
DOI: 10.1099/00207713-52-3-1007
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fatty acids as chemotaxonomic markers of the genera Anabaena, Aphanizomenon, Microcystis, Nostoc and Planktothrix (cyanobacteria).

Abstract: The cellular fatty acid content of 22 cyanobacterial strains belonging to the genera Anabaena, Aphanizomenon, Calothrix, Cylindrospermum, Nostoc, Microcystis and Planktothrix were analysed. The identities of the major peaks were confirmed by MS. Correspondence analysis of the data revealed three distinct groups formed by the Microcystis strains, the Nostoc/Planktothrix strains and the Anabaena/Aphanizomenon/Cylindrospermum strains. The Calothrix strain did not cluster with the other heterocystous cyanobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 33 publications
5
75
2
1
Order By: Relevance
“…On the other hand, the close position of the traditional genus Aphanizomenon to the planktic Anabaena-types (subg. Dolichospermum) was demonstrated (Iteman et al 2002;Gugger et al 2002aGugger et al , 2002bRajaniemi et al2005;Willame et al in press). Moreover, the both genera, planktic Anabaena and Aphanizomenon, were found heterogeneous, and were divided in several subclusters, spread among diverse groups of the planktic Anabaena/Aphanizomenon complex.…”
Section: Concept Of Generamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the close position of the traditional genus Aphanizomenon to the planktic Anabaena-types (subg. Dolichospermum) was demonstrated (Iteman et al 2002;Gugger et al 2002aGugger et al , 2002bRajaniemi et al2005;Willame et al in press). Moreover, the both genera, planktic Anabaena and Aphanizomenon, were found heterogeneous, and were divided in several subclusters, spread among diverse groups of the planktic Anabaena/Aphanizomenon complex.…”
Section: Concept Of Generamentioning
confidence: 99%
“…In light of the above discussion it is useful to point out studies that combine the morphological and molecular approaches discussed above. Some key studies have been published, e.g., by Flechtner et al (2002) on Spirirestis, Iteman et al (2002), Gugger et al (2002aGugger et al ( , 2002b, Rajaniemi et al (2005aRajaniemi et al ( , 2005b and Willame et al (in press) on the planktic bloom-forming Anabaena /Aphanizomenon complex ( Fig. 10), Suda et al (2002) on planktic oscillarioid species, Hrouzek et al (2005) on Nostoc, Komárek et al (2004) on Cyanothece and Cyanobacterium, Gugger and Hoffmann (2004) on the stigonematalean types, and Abed et al (2002) on the new genus Halomicronema.…”
Section: Combined Molecular and Traditional Approachmentioning
confidence: 99%
“…Cyanobacteria are very variable in their fatty acid compositions, with marked diVerences occurring even in the same genus (Gugger et al 2002). Due to the coexistence of diVerent cyanobacteria species in the Baltic Sea, it is not easy to identify a clear trophic signal.…”
Section: Trophodynamicsmentioning
confidence: 99%
“…Many studies reported that a characteristic fatty acid pattern of cyanobacteria consists of 16:0, 16:1, 18:2(n¡6) and 18:3(n¡3) (e.g. Murata and Nishida 1987 and references therein, Vargas et al 1998;Gugger et al 2002). The simultaneous occurrence of 18:3(n¡3) and 18:2(n¡6) with cyanobacteria and chlorophytes in the seston, indicated that elevated amounts of these fatty acids in P. acuspes were due to an augmented use of cyanobacteria in summer, since chlorophytes were only of minor importance.…”
Section: Trophodynamicsmentioning
confidence: 99%
“…Pediastrum especially between 1965-1970Stadelmann et al, 2002;van der Knaap et al, 2000) are indeed not reputed producing long-chain saturated FAs (Gugger et al, 2002;Caudales and Wells, 1992;Parker et al, 1967;Blokker et al, 1998).…”
Section: Csia Of Lake Sedimentsmentioning
confidence: 99%